2006
DOI: 10.1086/501072
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan for Loci Predisposing to Anxiety Disorders Using a Novel Multivariate Approach: Strong Evidence for a Chromosome 4 Risk Locus

Abstract: We conducted a 10-centimorgan linkage autosomal genome scan in a set of 19 extended American pedigrees (219 subjects) ascertained through probands with panic disorder. Several anxiety disorders--including social phobia, agoraphobia, and simple phobia--in addition to panic disorder segregate in these families. In previous studies of this sample, linkage analyses were based separately on each of the individual categorical affection diagnoses. Given the substantial comorbidity between anxiety disorders and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 44 publications
4
60
0
2
Order By: Relevance
“…This signifies that a linkage signal can be not only due to the disease, but also due to other characteristics of a clinical sample. As our significant linkage result was also previously found in a clinical sample, 12 the region on chromosome 14 is possibly associated with the whole spectrum of general anxiety, that is from the normal to the clinical range.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This signifies that a linkage signal can be not only due to the disease, but also due to other characteristics of a clinical sample. As our significant linkage result was also previously found in a clinical sample, 12 the region on chromosome 14 is possibly associated with the whole spectrum of general anxiety, that is from the normal to the clinical range.…”
Section: Discussionsupporting
confidence: 87%
“…For the same region at chromosome 14, Kaabi et al 12 reported a significant linkage result (nominal P = 0.005 and empirical P = 0.04). However, after adjusting for sib-pair age differences, the signal disappeared (nominal P = 0.07, empirical P not given).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…21 The Yale group has published four analyses of various ANX phenotypes. We used the results from Kaabi et al, 22 which analyzed linkage to a multivariate 'fuzzy clustering' phenotype that combined information from PD and social, specific, and agoraphobias. Finally, we included data from the primary PD linkage analysis published by the Iowa group.…”
Section: Data Sources Samples and Measuresmentioning
confidence: 99%